b-Bistochastic quadratic stochastic operators and their properties - Mukhamedov, Farrukh; Embong, Ahmad Fadillah (Institute of Physics Publishing, 2016)
In the present paper, we consider a class of quadratic stochastic operators (q.s.o.)called b-bistochastic q.s.o. We study several descriptive properties of b-bistochastic q.s.o. It turns out that, upper triangular stochastic matrix defines a linear b-stochastic operator. This allowed us to find some sufficient conditions on cubic stochastic matrix to be a b−bistochastic q.s.o.